P16 Factors influencing recurrence in patients undergoing laparoscopic treatment for early stage cervical cancer. (1st November 2019) - Casarin, J; Bogani, G; Pinelli, C; Papadia, A; Mueller, MD; Raspagliesi, F; Ghezzi, F
Abstract : Introduction/Background: Following the results of LACC trial, laparoscopic treatment for early stage cervical cancer has become matter of debate. In the present investigation we aimed to evaluate predictors of recurrence after laparoscopic surgery for early stage cervical cancer (CC). Methodology: A multi-centre retrospective study was conducted among patients who underwent laparoscopic radical surgery for FIGO 2009 stage IA (positive LVSI) - IB1 at three referral gynecologic oncology centers, between January 2006 and June 2018. All patients had radical hysterectomy (B-C1) with or without lymph node dissection according with tumour characteristics. Surgical and oncological outcomes were analysed. Results: Among 186 patients who met the inclusion criteria, 16 (8, 6%) experienced recurrence (6 vault, 9 pelvis, 5 abdominal, 3 distant, 7 multiple), and 9 (4.8%) died of disease over the follow-up period (median follow-up 38.0 months). Surgical-related complications did not influence survival outcomes. All the recurrences occurred in stage Ib1 disease, which has been found to be the main predictor of recurrence (p=0.02), while no association between positive lymph node and relapse was detected. Patients who had preoperative conization (93, 50%) had a significant lower rate of recurrence compared to those who had biopsy (93, 50%) (1/93, 1, 1% vs. 15/93: 16, 1% p=0.0003). After stratification by FIGO stage, patients with Ib1 tumor undergoing conization had significant favourable DFS compared to those who had only biopsy (p=0.012). Conclusion: Preoperative conization might play a crucial role in patients undergoing laparoscopic treatment for early stage CC. Further studies are warranted to strength our finding. Disclosure: Nothing to disclose.